(untitled) (Bangladesh Journal of Pharmacology, 2016)
Cayratia trifolia is used as diuretic, in tumors, neuralgia and splenopathy. However, compounds depicting anti-ovarian cancer activities from this plant source have not yet been identified and structurally characterized till date. In the present study, X-ray structure of epifriedelanol, a bioactive compound, isolated from the ethanolic extract of the C. trifolia and its binding affinities against a few proteins (HER2, EGFR and CXCR4) that are reported to get overexpressed under ovarian cancer had been thoroughly studied by using molecular docking means. Binding affinities of the compound vis-à-vis that of carboplatin, a FDA approved drug to the ovarian cancer, to interact with the protein targets are quite impressive. The drug-likeness properties of the epifriedelanol and scope to develop the compound as a potent anti-ovarian cancer drug are discussed in this paper.